(untitled) - Whistman, Jonathan (Hoboken, New Jersey, 2016)
The Sales Boss: The Real Secret to Hiring, Training and Managing a Sales Team, is a comprehensive guide on how to create a winning sales team. In any business, nothing happens until somebody sells something. Nobody pays their mortgages, no kids get sent to college, and no retirements get funded until the salesperson is able to close business and get revenue coming in the door. In a company with a sales manager, the hiring, training and success of the sales people lay directly at the feet of the manager. The importance and significance of this role can well be illustrated by a recent study that shows that 95% of the CEOs in mid-size companies have at some point in their career filled the role of Sales Manager prior to being promoted to run the company. Clearly, this job matters. The hopes and dreams of the entire company depend on the job being done masterfully. The Sales Boss refers to a sales leader operating at peak performance and overseeing a team of people that outperforms the competition. Inside the cover of this book, the reader will begin a journey that will help them take a deep look into the psychology behind getting a team operating at the highest levels. A step-by- step guide to hiring, training, and managing the team follows this introduction and will leave the reader not only with an understanding of what needs to be done but with direct examples of how they can do it
Keywords: Quản lý bán hàng,Sales management